MICROCREDIT THROUGH SELF HELF GROUP FOR RURAL DEVELOPMENTIN THENI DISTRICT - Deepa, D.; Priyanka, G (International Journal of Psychosocial Rehabilitation, 2020)
The women empowerment has been recognized as a sine-qua-non for the growth of the Country and societal well-being. In order to bring, women into the mainstream of the economy and society, Indian Government has initiated numerous development programs for women. The essential savings have mobilized would be invested in productive activities, which in turn able to enhance the employability, income and output and the microcredit increasethe income would increase the purchasing power and effective demand among the community and thereby the standard of living and the economic development of the nation would progress.This study to be aimed to examine the factors influencing and impact of microcredit through SHGs for rural development in Theni District.This research is to be based on empirical and nature of the study.  The primary data will be collected from 50 Self Help Group Members in Theni District through an interview schedule under the Convenient Sampling Method.The found impacts are largely linked to personal and family issues, on account of the special power of the microcredit mechanism to improve the women’s standards of support. Social impacts, even though expected to be insignificant, are also revealed by the study.  The results confirm that microcredit has a significant impact on five dimensions of women's empowerment, setting out from economic security to the cognizance of social/legal matters.